Clinical research Myocardial performance index after surgical correction of ventricular septal defects - Baghdady, Yasser; Kamel, Yasser; Amar, Waleed (Archives of Medical Science, 2010)
Introduction: The myocardial performance index (MPI) has been described as a non-invasive Doppler measurement of ventricular function. The aim of this study was to assess MPI following surgical correction of ventricular septal defect (VSD) and to evaluate its impact on postoperative recovery. Material and methods: This is a prospective study involving 30 children (16 girls and 14 boys) operated on for VSD (group I). The control group (group II) consisted of 30 healthy children (age and sex matched). Results: We found that both the right and left ventricular (RV and LV) MPI correlated significantly with the ejection fraction (EF) (r = –0.49, p = 0.006, r = –0.51, p = 0.004, respectively). The LV EF and the LV FS were negatively correlated, while the left and right ventricular MPI was positively correlated with the: LVEDD (p = 0.000), the VSD size (p = 0.000), and the postoperative course of the patients in terms of the duration of ventilation (p = 0.000), the duration of use of inotropics (p = 0.000) and the duration of staying in the ICU (p = 0.000). By linear regression, the factors that correlated with the postoperative course of VSD surgery were the RV MPI pre-surgery, MPI 2 days after surgery and the ejection fraction (p = 0.000). Conclusions: Myocardial performance index is a useful index for measurement of the left and right ventricular function. It correlates significantly with the ejection fraction, fractional shortening, VSD size, and the left ventricular size. It also significantly predicts the outcome of VSD surgery.